New species of Rhorus Förster, 1869 (Hymenoptera: Ichneumonidae: Ctenopelmatinae) from South Korea - Kasparyan, D.r.; Choi, Jin-Kyung; Lee, Jong-Wook (Zootaxa, 2016)
A new ichneumonid-species Rhorus koreensis sp. nov. is described from South Korea. Monoblastus jinjuensis Lee et Cha, 1993 described from South Korea is transferred to Rhorus (new combination). Only Rh. takagii (Uchida, 1931) is recorded previously from South Korea. Rhorus nigritarsis (Hedwig, 1956) is recorded for the first time from South Korea. A key to the four South Korean species are provided.